Understanding, Thinking and Exploring: Cultural Teaching of Vocabularies under the New English Curriculum Standard - Yangyang Yu (International Journal of Humanities and Education Development (IJHED), 2022)
English vocabulary plays an important role in English language learning, and the methods of vocabulary acquisition also have a profound impact on its effect. Under the guidance of the New Curriculum Standard, the cultivation of cultural awareness is also an important part of the core literacy of English subjects, so it will be an inevitable trend of English vocabulary learning to apply the study of cultural awareness to vocabulary acquisition. In actual vocabulary teaching, to truly grasp the core essence of cultural awareness, teachers should recognize the shortcomings of cultural teaching and vocabulary teaching, and under the guidance of the core literacy of English subjects, combine vocabulary teaching with the transmission of cultural knowledge, aiming at exploring the English cultural connotation behind vocabulary, promoting the effective implementation of vocabulary and cultural teaching, and providing some reference suggestions for vocabulary cultural teaching